Effects of the evolving early Moon and Earth magnetospheres - Green, James; Boardsen, Scott; Dong, Chuanfei (Frontiers in Astronomy and Space Sciences, 2023)
Recently it has been identified that our Moon had an extensive magnetosphere for several hundred million years soon after it was formed when the Moon was within 20 Earth Radii (RE) from the Earth. Some aspects of the interaction between the early Earth-Moon magnetospheres are investigated here. The authors extended the analysis of Green et al. (2020) by mapping the interconnected field lines between the Earth and the Moon and investigating how the early lunar magnetosphere affects the magnetospheric dynamics within the coupled magnetospheres. So long as the magnetosphere of the Moon remains strong as it moves away from the Earth in the antialigned dipole configuration, the extent of the Earth’s open field lines decreases. As a result, at times it significantly changes the structure of the field-aligned current system, pushing the polar cusp significantly northward, and forcing magnetotail reconnection sites into the deeper tail region. In addition, the combined magnetospheres of the Earth and the Moon greatly extend the number of closed field lines enabling a much larger plasmasphere to exist and connecting the lunar polar cap with closed field lines to the Earth. That configuration supports the transfer of plasma between the Earth and the Moon potentially creating a time capsule of the evolution of volatiles with depth. This paper only touches on the evolution of the early Earth and Moon magnetospheres, which has been a largely neglected space physics problem and has great potential for complex follow-on studies using more advanced tools and due to the expected new lunar data coming in the next decade through the Artemis Program.